Model Problem Based Learning, Guided Inquiry, dan Kemampuan Berpikir Kritis Matematis - Yanti, Oktavia Filda; Prahmana, Rully Charitas Indra (UIN Sunan Ampel Surabaya, 2017)
This research aims to determine differences in mathematical critical thinking skills between students who obtain mathematics learning using Problem Based Learning (PBL) and Guided Inquiry model. The research method used quasi-experimental with matching-only posttest-only control group design which implemented in one of the Junior High School of Yogyakarta. The instrument used is a valid test instrument namely posttest with descriptive evaluation. The result of this research showed that there is a difference of mathematical critical thinking skills between students who obtain mathematics learning using PBL model and students who obtain mathematics learning using guided inquiry model. Furthermore, the average of mathematical critical thinking skills between a student who obtains mathematics learning using problem based learning model is higher than students who obtain mathematics learning using guided inquiry model.